A comparative study regarding the perception of junior high school students from selected private and public schools in Antipolo towards Library and Information Science as a career - Toquero, Michael J. (School of Library and Information Studies, University of the Philippines Diliman, 2008)
This study is entitled "A Comparative Study Regarding the Perception of Junior High School Students from Selected Private and Public Schools in Antipolo towards Library and Information Science as a Career". The study aims to find out the perceptions of 3rd year public and private high school students towards LIS as a profession; the factors that influence these perceptions toward their choice of profession and how these perceptions affect their choice of LIS as a career. Two hundred and thirty-five respondents from six different schools; three from public schools and three from private schools were used as respondents for this study. A questionnaire was used as instrument for data gathering.